Agility and the transition from uncertainty to recovery: the Indian IT industry and COVID-19 - Premilla D'Cruz; Ernesto Noronha (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
This paper reports a study of how the Indian IT industry navigated the COVID-19 pandemic. Agility emerged as the crucial determining factor aiding the industry's successful survival. IT organisations' agility, facilitated by the state's response to the pandemic and by both their anticipation of the lockdown and their technological capabilities, helped them overcome the crisis. The slowdown forced firms to downsize, reduce bench strength, freeze wages and intensify work, while deferring client payments. When the economy recovered, high attrition, termed 'The Great Resignation', forced employers to increase wages. Employers were unable to compel employees to return to the office, despite facing issues relating to organisational culture, data security and moonlighting. Remote working helped employees maintain work-life balance and save on cost of living, forcing employers to provide a hybrid option.
Keywords: L86; J49; L25; F69; 330; agility; COVID-19; employer-employee relations; IT industry; organisational performance; state